Historia de la Comisión Codificadora de 1882 y el Código Civil de 1888 - Arias Castro, Tomás Federico (2013)
This historical research article exposes the reader a thorough and detailed study about the different stages and historical events that came together for the creation of the famed Codifying Commission of Jurists, 1882, considered the most representative legal body in our history. It also recounts the details that led to his main work: the Civil Code of 1888, which force to the present.